2023
DOI: 10.5194/egusphere-2023-909
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence of cryptic methane cycling and non-methanogenic methylamine consumption in the sulfate-reducing zone of sediment in the Santa Barbara Basin, California

Abstract: Abstract. The recently discovered cryptic methane cycle in the sulfate-reducing zone of marine and wetland sediments couples methylotrophic methanogenesis to anaerobic oxidation of methane (AOM). Here we present evidence of cryptic methane cycling activity within the upper regions of the sulfate-reducing zone, along a depth transect within the Santa Barbara Basin, off the coast of California, USA. The top 0–20 cm of sediment from each station was subjected to geochemical analyses and radiotracer incubations us… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Evidence showed that aerobic methane-oxidizing bacteria could be adapted to a wide range of oxygen concentrations in seasonally hypoxic coastal waters (Steinle et al, 2017). A recent study demonstrated that seasonal deoxygenation could prompt the activity of the methanotroph community and methane consumption rates in a dynamic marine environment of the Santa Barbara Basin (Krause et al, 2023), but the effect of oxygen on methanotrophy at the ecosystem scale was likely indirect (Qin et al, 2022). However, the waters of the YS and ECS were fully oxygenated (oxygen concentrations >220 μM) so oxygen did not limit MOx and no correlation with methanotrophic activity was observed in these areas.…”
Section: Spatial Variability and Environmental Controls Of Mox In Ys ...mentioning
confidence: 99%
“…Evidence showed that aerobic methane-oxidizing bacteria could be adapted to a wide range of oxygen concentrations in seasonally hypoxic coastal waters (Steinle et al, 2017). A recent study demonstrated that seasonal deoxygenation could prompt the activity of the methanotroph community and methane consumption rates in a dynamic marine environment of the Santa Barbara Basin (Krause et al, 2023), but the effect of oxygen on methanotrophy at the ecosystem scale was likely indirect (Qin et al, 2022). However, the waters of the YS and ECS were fully oxygenated (oxygen concentrations >220 μM) so oxygen did not limit MOx and no correlation with methanotrophic activity was observed in these areas.…”
Section: Spatial Variability and Environmental Controls Of Mox In Ys ...mentioning
confidence: 99%